The future of grocery stores : Omnichannel and AI technologies and Next-Generation Brick-and-Mortar Grocery Stores - Neurauter, Clemens (2022)
In recent years the grocery retail industry has been experiencing tremendous change, driven mainly by advances in technology. Traditional brick-and-mortar grocery stores are under threat from industry disruptors who incorporate new technologies into their business models and operate with online channels. Therefore, this paper introduces omnichannel and artificial intelligence (AI) use cases as factors influencing the future success of brick-and-mortar grocery stores. To identify critical drivers for success, semi-structured expert interviews were conducted to discover how grocers can implement an omnichannel strategy and combine various AI technologies to remain competitive. Furthermore, a customer survey tested the acceptance of specific use cases and scrutinized the resulting increase or decrease in shopping frequency due to omnichannel in conjunction with AI. The analysis indicates an upcoming change in the grocery industry. A move towards a combination of an online and offline world is rising. Moreover, use cases like online shopping, personalized prices and offers, and cashier-free checkouts have the highest potential to increase the points-of-delight by consumers while grocery shopping. Therefore, grocers must adopt an omnichannel strategy and incorporate several AI-driven technologies to increase profits and remain competitive.